Monocarboxylate Transporter 8 Deficiency: From Pathophysiological Understanding to Therapy Development - van Geest, Ferdy S.; Gunhanlar, Nilhan; Groeneweg, Stefan; Visser, W. Edward (Frontiers in Endocrinology, 2021)
Genetic defects in the thyroid hormone transporter monocarboxylate transporter 8 (MCT8) result in MCT8 deficiency. This disorder is characterized by a combination of severe intellectual and motor disability, caused by decreased cerebral thyroid hormone signalling, and a chronic thyrotoxic state in peripheral tissues, caused by exposure to elevated serum T3 concentrations. In particular, MCT8 plays a crucial role in the transport of thyroid hormone across the blood-brain-barrier. The life expectancy of patients with MCT8 deficiency is strongly impaired. Absence of head control and being underweight at a young age, which are considered proxies of the severity of the neurocognitive and peripheral phenotype, respectively, are associated with higher mortality rate. The thyroid hormone analogue triiodothyroacetic acid is able to effectively and safely ameliorate the peripheral thyrotoxicosis; its effect on the neurocognitive phenotype is currently under investigation. Other possible therapies are at a pre-clinical stage. This review provides an overview of the current understanding of the physiological role of MCT8 and the pathophysiology, key clinical characteristics and developing treatment options for MCT8 deficiency.